New fertilisers policy: a practical approach - Sanjay Kumar (1999)
The fertiliser industry rejected the report of the Hanumantha Rao Committee on pricing of fertilisers on the ground that a uniform pricing policy cannot be applied to an industry that is so heterogeneous in its structure due to various factors which were exogenous to the industry. This article examines the arguments of the industry. It also examines the recommendations of the committee and tries to meet some of the valid criticisms of the industry and work out a modified price following the long-range marginal costing principle. The new price will improve the acceptability of the report and encourage new capacity addition. - Reproduced
Keywords: Fertilizers - India; Fertilizers